APLIKASI GREEN ARCHITECTURE PADA RUMAH GEDONG - Anisa, . (INERSIA lnformasi dan Ekspose Hasil Riset Teknik Sipil dan Arsitektur, 2016)
ABSTRACT Green architecture is a scheme process in lessening unfavourable environmental impact, increase comfort of man by increasing efficiency, and reduction of usage of resource, energy, usage of farm, and management of effective garbage in architecture level (Kwok Allison dalam Ming Kok, Cheah, 2008). This research result, that is found some element in houses gedong which are evidence green architecture. (1) vegetation optimalisation which form out of two yard at house gedong; (2) The many building side which diekspos and mass configuraton in site; (3) Design fasade building, possible to maximize natural atmosphere and illumination; (4) Terrace;core and teritis. Terrace amounting to multiple and teritis the in all heat Create building side to depend and don’t coming into house; (5) Draught with crossed ventilation, presentation of from aperture in the form of door, window, roster and other aperture at part of building wall. Keyword: Green architecture, rumah Gedong